2002
DOI: 10.1073/pnas.222348099
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of c-Src to large conductance voltage- and Ca 2+ -activated K + channels as a new mechanism of agonist-induced vasoconstriction

Abstract: (2), or as a negative feedback mechanism to limit Ca 2ϩ entry by hyperpolarizing the plasma membrane and closing voltagedependent Ca 2ϩ channels (3) previously opened by pressure (4) or vasoconstrictors like 5-hydroxytriptamine (5-HT) and Angiotensin II (AngII) (5, 6). In vitro evidence suggests that MaxiK also may play a role in vasoconstriction as it is inhibited by the potent constrictors AngII (7) and thromboxane A2 (8) in bilayers. However, the functional role of MaxiK channels in agonist-induced contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
127
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 47 publications
13
127
2
Order By: Relevance
“…In apparent contrast to our finding that c-src overexpression enhances the Ca 2ϩ sensitivity of mSlo, the data of Alioua et al (29) suggest that BK channel phosphorylation by endogenous c-src leads to inhibition of BK channel activity in VSM. Although different isoforms of the BK channel (mSlo and hSlo) were used in our respective studies, the two channels have ϳ96% predicted amino acid identity (GenBank TM accession numbers U09383 and U11058) with differences occurring only at two splice insert sites that do not appear to be critical for c-src phosphorylation.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In apparent contrast to our finding that c-src overexpression enhances the Ca 2ϩ sensitivity of mSlo, the data of Alioua et al (29) suggest that BK channel phosphorylation by endogenous c-src leads to inhibition of BK channel activity in VSM. Although different isoforms of the BK channel (mSlo and hSlo) were used in our respective studies, the two channels have ϳ96% predicted amino acid identity (GenBank TM accession numbers U09383 and U11058) with differences occurring only at two splice insert sites that do not appear to be critical for c-src phosphorylation.…”
Section: Discussioncontrasting
confidence: 99%
“…Alioua et al (29) found that c-src directly phosphorylated heterologously expressed hSlo and produced a rightward shift in the G-V relationship (29). A more likely difference between our results and those of Alioua et al (29) could be related to the degree of BK channel phosphorylation induced by c-src co-expression under both experimental conditions. As shown in Fig.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…In Drosophila, two cytosolic regulatory proteins, Slob and dSLIP, and two protein kinases, Src and PKAc, are able to assemble with the slo ␣-subunit (27)(28)(29). In vertebrates, however, only kinases, such as Src and Syk, have been reported to interact with this subunit (30)(31)(32). To seek other proteins that associate with K Ca channels and mediate their presynaptic targeting, we used yeast two-hybrid screening to search a cDNA library made from sensory epithelia of the chicken's cochlea.…”
mentioning
confidence: 99%